Precipitation Chemistry and Occurrence of Acid Rain over the Oil-Producing Niger Delta Region of Nigeria - John Kanayo Chukwu Nduka; Orish Ebere Orisakwe (The Scientific World Journal)
This study investigated the nitrate, sulfate, total dissolved solid (TDS), electrical conductivity, total hardness (TH), and bicarbonates of rainwater samples collected from Warri and Port Harcourt between April–June, July–August, and September–October of 2005 and 2006 to depict onset of rainy season, mid-rainy season, and end of rainy season for the two major crude oil–producing cities of the Niger Delta region of Nigeria (although Port Harcourt is also noted for non-oil manufacturing industries). The same was done in Awka, a non-oil producing city in the hinterland of southeastern Nigeria. In each of the cities, rain samples were collected from three points in a triangular equilibrium using a clean plastic basin fastened to a table 2 m above ground level and 115 m away from tall buildings and trees. The parameters were determined after filtering, using their respective standard methods. Averages of 1.50, 1.81, 1.13 and 2.14, 1.50, 1.86 mg/l of nitrate for April–June, July–August, and September–October were recorded for Warri in 2005 and 2006, respectively. While 15.21, 3.23, 22.31 and 20.89, 9.96, and 14.27 mg/l were recorded in Port Harcourt. Sulfate levels for Warri and Port Harcourt for the same periods are follows: 1.38, 1.88, 1.06, 1.50, 1.43, 1.50 and 2.64, 1.15, 5.88, 4.73, 1.90, 1.55 mg/l, respectively. Nitrate levels were higher than sulfate. Other parameters include TDS (5.44, 4.79, 3.30 and 7.63, 3.69, 2.56 mg/l for Warri in 2005 and 2006; 12.57, 2.07, 25.214 and 28.87, 6.73, 7.80 mg/l for Port Harcourt for the same periods). Other parameters also varied in that order for the 2 years in same cities. Crude oil exploration and gas flaring in the Niger Delta, and multiplicity of cottage industries in Awka, impacted on the inorganic ion pollution of the rainwater. This may have public health implications in the region.